1, 2, 4‐trihydroxynaphthalene‐2‐O‐β‐D‐glucopyranoside delays amyloid‐β42 aggregation and reduces amyloid cytotoxicity. (26th March 2018) - Dhouafli, Zohra; Leri, Manuela; Bucciantini, Monica; Stefani, Massimo; Gadhoumi, Hamza; Mahjoub, Borhane; Ben Jannet, Hichem; Guillard, Jérôme; Ksouri, Riadh; Saidani Tounsi, Moufida; Soto, Claudio; Hayouni, El Akrem
Abstract: Presently, misfolding and aggregation of amyloid‐β42 (Aβ42 ) are considered early events in Alzheimer's disease (AD) pathogenesis. The use of natural products to inhibit the aggregation process and to protect cells from cytotoxicity of early aggregate grown at the onset of the aggregation path is one of the promising strategies against AD. Recently, we have purified a new powerful antioxidant and inhibitor of Aβ42 aggregation from the leaves of Lawsonia inermis . The new compound was identified as a new Lawsoniaside; 1, 2, 4‐trihydroxynaphthalene‐2‐O‐β‐D‐glucopyranoside (THNG). Herein, we show that THNG interferes with Aβ42 aggregation, inhibits its conformational change to a β‐sheet‐rich structure, decreases its polymerization into large fibrillar species, reduces oxidative stress, and aggregate cytotoxicity. These results indicate that THNG has great potential as a neuroprotective and therapeutic agent against AD. © 2018 BioFactors, 44(3):272–280, 2018